2022
DOI: 10.1161/hypertensionaha.122.19633
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiovascular Health Score Trajectory With Incident Myocardial Infarction in Hypertensive Patients

Abstract: Background: The association between changes in cardiovascular health score (CHS) over time and myocardial infarction (MI) risk in hypertensive patients remains unclear. Method: This was a prospective study comprising 17 374 hypertensive patients from the Kailuan study cohort who underwent 3 surveys and were identified to be free of MI, stroke, or cancer from 2006 to 2010. CHS consisted of 7 cardiovascular health metrics (plasma glucose, total cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Although no direct parallels exist, the trajectory of cardiovascular health scores has been widely studied since the American Heart Association proposed the 7 cardiovascular health metrics. Various studies have demonstrated the efficacy of cardiovascular health trajectories in predicting CVD development [ 15 , 26 , 27 ], indirectly supporting our perspective.…”
Section: Discussionsupporting
confidence: 80%
“…Although no direct parallels exist, the trajectory of cardiovascular health scores has been widely studied since the American Heart Association proposed the 7 cardiovascular health metrics. Various studies have demonstrated the efficacy of cardiovascular health trajectories in predicting CVD development [ 15 , 26 , 27 ], indirectly supporting our perspective.…”
Section: Discussionsupporting
confidence: 80%
“…Prior studies evaluating the trends of CVH over 20 years (5 CVH trajectories: low-stable, moderate-decreasing, moderate-increasing, high-stable I, and high-stable II) indicated that improvement or attainment of better CVH metrics through midlife to late life was associated with a lower CVD prevalence and better cardiovascular structure and function [ 33 , 34 ]. Recently, a study during a follow-up of 10 years showed that high-stable groups could be decreased 64–76% risk of MI in reference to the low-stable group [ 18 ]. Similarly, studies also demonstrated that the elevated-stable group could reduce the risk of arterial stiffness (HR: 0.23; 95% CI 0.18–0.29) [ 35 ], whereas the declining CVH status group was associated with a higher risk of carotid intima-media thickness (HR: 2.40; 95% CI 1.30–4.50) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies examined the association between CVH score trajectories or CVH metrics change over time and CVDs or mortality during follow-up [ 15 17 ]. Previous studies indicated that participants with the high-stable II trajectory of CVH score had 76–79% decreased risk of CVDs and mortality compared with the low-stable group [ 16 , 18 ]. These findings suggest the importance of maintaining a higher CVH score or ideal CVH metrics for preventing CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…The Kailuan study is a large community-based prospective cohort study that is being conducted in Tangshan, China and aims to identify the risk factors for chronic non-communicable diseases. The research design and methods of the Kailuan study have been described previously [ 17 , 18 ]. In brief, the Kailuan study started in 2006–2007, a total of 101,510 participants were recruited for the baseline survey, and they were followed up every 2 years.…”
Section: Methodsmentioning
confidence: 99%